Treatment of heterozygous familial hypercholesterolemia: what does the future hold?. Issue 11 (1st November 2020) - Polychronopoulos, Georgios; Tziomalos, Konstantinos
ABSTRACT: Introduction: Heterozygous familial hypercholesterolemia (heFH) is a common metabolic disease associated with increased cardiovascular risk. Despite treatment with the currently available lipid-lowering agents (statins, ezetimibe, and proprotein convertase subtilisin/kexin type 9 inhibitors), a substantial proportion of patients with heFH does not achieve low-density lipoprotein cholesterol (LDL-C) targets. Areas covered: The PubMed database was reviewed for relevant papers published up to August 2020. The safety and efficacy of novel agents, namely inclisiran and bempedoic acid, that lower LDL-C levels and might be useful in the management of patients with heFH are discussed. Expert opinion: The prolonged lipid-lowering effect of inclisiran might improve adherence to treatment in patients with heFH. Bempedoic acid provides additional reductions in LDL-C levels in patients on high-intensity statin treatment; oral administration of this agent might be attractive to some patients. However, it is important to evaluate the effects of these agents on cardiovascular morbidity before they are incorporated in the management of heFH. The cost/benefit of treatment should also be considered, given the increasing complexity of lipid-lowering treatment.